Functional outcome in operated patients of multilevel lumbar canal stenosis and use of HRQoL role in depicting the anxiety and its correlation with the pain - Ajay Kumar Singh (SpringerOpen, 2021)
Abstract Background Lumbar canal stenosis (LCS) is a degenerative spinal disease of elderly people, and it not only impairs the mechanical activity but also alters the economic and mental status of the patients indirectly. This is single-center observational prospective study conducted for 2 years and included 30 consecutive operated patients of multilevel LCS patients and excluded the patients with single-level LCS, with primary LCS or with grade II subluxation. We analyzed the various measurement indices used for the surgical outcome assessment as ED-5D 5L and OLBPDI (Oswestry low back pain disability index). Statistical analysis was done using SPSS (Statistical Package for Social Sciences) Version 21.0 statistical Analysis Software. The independent t test, post hoc analysis, Wilcoxon signed rank statistic test and RM-ANOVA test were also applied. Result Most patients have improvement in pain and all the components of HRQoL (health-related quality of life) after surgery, which was further improved in mean follow-up of 1 year. Our study also suggested that the patients with higher anxiety/depression have higher pain intensity and low HRQoL, which was persistent in postoperative period (p < .001). Conclusion ED-5D 5L and OLBPD are good indices to assess all the components of quality of life and give valuable information overall. Anxiety has shown important correlation with the pain component in both preoperative and postoperative phase.